Penguatan Solidaritas Sosial Masyarakat melalui Kegiatan Perayaan Hari Kemerdekaan di Desa Penagan Ratu - Maya Siti Anisa; Ary Forniawan; Siti Zumrotus Sa’adah (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
In this Community Service Program (KKN) activity, the main goal is to strengthen social solidarity among the residents through the celebration of Indonesia’s Independence Day in Penagan Ratu Village. Social solidarity is one of the key factors in maintaining harmony and togetherness within the community. However, in today’s modern era, the spirit of cooperation and mutual assistance tends to decline due to individualism and people’s busy daily routines. Therefore, the Independence Day celebration serves as a strategic moment to revive the sense of brotherhood, unity, and social awareness among the villagers. This program was carried out with the active participation of all community members, including village officials, youth organizations (karang taruna), women’s groups, children, and teenagers. Various activities were conducted such as community clean-up (kerja bakti), traditional games, art performances, and a local MSME (UMKM) bazaar. The implementation method was participatory, emphasizing the active involvement of the community in every stage. The results of the program showed a high level of community participation, stronger social bonds, and an increase in the spirit of mutual cooperation. Moreover, the event brought a positive impact through the empowerment of local MSMEs. Thus, the Independence Day celebration was not merely ceremonial, but also served as an effective medium to strengthen social solidarity, fostering a more cohesive, respectful, and socially aware community in Penagan Ratu Village.